RuO2 center dot nH(2)O nanoparticles anchored on carbon nano-onions: an efficient electrode for solid state flexible electrochemical supercapacitor - Muniraj, Vedi Kuyil Azhagan; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ACS Sustainable Chemistry & Engineering, 2016)
A flexible solid state electrochemical capacitor based on hydrous RuO2 nanoparticles, supported onto the nonporous and highly accessible ion adsorptive carbon nano onions (CNOs), is fabricated in a novel process of modifying a conducting carbon paper to a flexible conducting substrate, separated with a poly(vinyl alcohol)/H2SO4 gel electrolyte. The sol-gel technique tends to form homogeneously dispersed RuO2 nanoparticles with the average size of similar to 2.3 nm on the positive surface curvatures of multilayer fullerene (CNOs), which helps the high diffusivity of ions in both the aqueous and solid state gel electrolytes. The flexible substrate worked excellently as an electrical conductor as well as a stable mechanical support. This solid state flexible energy storage device showed a maximum energy density of 10.62 Whkg(-1) and a maximum power density of 4.456 kWkg(-1) for the hydrous RuO2/CNOs nanocomposite with 94.47% cycling stability even after 4000 cycles.
Keywords: Carbon nano-onions; Electrochemical capacitor; Flexible conducting substrate; Flexible energy storage device; Hydrous ruthenium oxide nanoparticles